Self Harm and Suicide in Adolescents - M. Fardi Anugrah; Khaula Karima; Ni Made Sri Padma Puspita; Nurul Aulia Binti Amir; Agustine Mahardika (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Self harm is also called Non-Suicidal Self-Injury (NSSI). NSSI is defined as intentional self-injurious behavior to cause minor bodily harm without suicidal intent. Self-harm is strongly associated with suicidal thoughts and approximately 27-30% of adolescents with NSSI have reported suicide attempts. Based on the explanation above, the author is interested in discussing self-harm and suicide to explore the definition and management of self-harm and suicidal behavior in adolescents. In writing this literature review, we used a literature study method from various references and focused on discussions about self-harm and suicide. The search engines used were PubMed, ProQuest, and Google Scholar with the keywords